Rola audytu wewnętrznego w procesie zarządzania jednostką sektora finansów publicznych na przykładzie urzędu wojewódzkiego w Łodzi - Szydłowski, Cezary (The Role of an Internal Audit in the Process of Finance Sector Entities Management, on the Example of the Łódź Voivodeship Office in Łódź, 2008)
In the result of the amendments which were made to the Act of 26 November 1998 on Public Finance, during the EU-Poland negotiations within ''financial control" chapter, an internal audit was established. The support of the management process in organization is the main purpose of an internal audit. In each organization the risk management plays a vital role. This risk can not be completely eliminated but should be identified and played down. Internal audit plays a fundamental role in this process. The reduction of public administration costs can be only achieved by the effective management of the public fund. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 519-529